Proceedings of the 6th International Conference on Community Development (ICCD 2019) 2019
DOI: 10.2991/iccd-19.2019.49
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurship Competence on Micro Business Performance

Abstract: This research focuses on entrepreneurial competencies required by traditional herbal medicine sellers, how they can survive against competition and crisis, and how they realize that they have entrepreneurial competencies like those of other successful entrepreneurs. Increasing entrepreneurial competence can improve the performance of microbusinesses, both financially and non-financially. Using a qualitative research method, this study seeks to determine the entrepreneurship competency model that has an impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…(Al Mamun et al, 2019;Barazandeh et al, 2015;Dhamayantie & Fauzan, 2017;Ferreras-garcia & Hernández-lara, 2019;Sungkawati, 2019) Direct and Indirect Influence Based on the results of the study, it was concluded that there was an influence between Knowledge ( 𝑋 1 ) and Individual Ability ( 𝑋 3 ) on Business Performance (Y). To see more about the magnitude of the direct and indirect effects of each variable, it is presented in Table 4.12 the details of the direct and indirect effects are as follows: Mamun et al, 2019;Barazandeh et al, 2015;Dhamayantie & Fauzan, 2017;Ferreras-garcia & Hernández-lara, 2019;Sungkawati, 2019) The actual influence of the Individual Ability variable ( 𝑋 3 )on Business Performance (Y) is 0.0021. It means that Individual Ability ( 𝑋 3 )directly affects Business Performance (Y) is 0.0001.…”
Section: Total Effect Testmentioning
confidence: 98%
See 4 more Smart Citations
“…(Al Mamun et al, 2019;Barazandeh et al, 2015;Dhamayantie & Fauzan, 2017;Ferreras-garcia & Hernández-lara, 2019;Sungkawati, 2019) Direct and Indirect Influence Based on the results of the study, it was concluded that there was an influence between Knowledge ( 𝑋 1 ) and Individual Ability ( 𝑋 3 ) on Business Performance (Y). To see more about the magnitude of the direct and indirect effects of each variable, it is presented in Table 4.12 the details of the direct and indirect effects are as follows: Mamun et al, 2019;Barazandeh et al, 2015;Dhamayantie & Fauzan, 2017;Ferreras-garcia & Hernández-lara, 2019;Sungkawati, 2019) The actual influence of the Individual Ability variable ( 𝑋 3 )on Business Performance (Y) is 0.0021. It means that Individual Ability ( 𝑋 3 )directly affects Business Performance (Y) is 0.0001.…”
Section: Total Effect Testmentioning
confidence: 98%
“…Indirect influence is through the Individual Ability variable 𝑋 3 )(Y) through Knowledge ( 𝑋 1 )of 0.002. (Al Mamun et al, 2019;Barazandeh et al, 2015;Dhamayantie & Fauzan, 2017;Ferreras-garcia & Hernández-lara, 2019;Sungkawati, 2019).…”
Section: Total Effect Testmentioning
confidence: 99%
See 3 more Smart Citations